Cumulative prospect theory and deferred annuities. (27th June 2019) - Chen, Anran; Haberman, Steven; Thomas, Stephen
Abstract : Purpose: Although it has been proved theoretically that annuities can provide optimal consumption during one's retirement period, retirees' reluctance to purchase annuities is a long-standing puzzle. The purpose of this paper is to use behavioral model to analyze the low demand for immediate annuities. Design/methodology/approach: The authors employ cumulative prospect theory (CPT), which contains both loss aversion and probability transformations, to analyze the annuity puzzle. Findings: The authors show that CPT can explain the unattractiveness of immediate annuities. It also shows that retirees would be willing to buy a long-term deferred annuity at retirement. By considering each component from CPT in turn, the loss aversion is found to be the major reason that stops people from buying an annuity while the survival rate transformation is an important factor affecting the decision of when to receive annuity incomes. Originality/value: This paper identifies CPT as one of the reasons for the low demand of immediate annuities. It further suggests that long-term deferred annuities could overcome behavioral obstacles and become popular among retirees.